(untitled) (Dermatology Reports, 2022)
Regorafenib is an oral multikinase inhibitor targeting several tyrosine kinase receptors including BRAF and epidermal growth factor receptor (EGFR) and is approved as a third-line treatment for metastatic gastrointestinal stromal tumor (GIST). While acneiform eruptions have been observed in patients receiving other BRAF and EGFR inhibitors, the commonly reported adverse reactions to regorafenib are fatigue and palmar-plantar erythrodysesthesia. Herein, we report, to the best of our knowledge, the first case who presented with a severe acneiform eruption 24 months after beginning regorafenib for the treatment of GIST. A 61-year-old woman developed GIST with multiple liver metastases, and she was treated with imatinib and sunitinib. However, these therapies were discontinued, and regorafenib was administered. Twenty-four months after beginning regorafenib, she developed an acneiform eruption on her back. Histopathologic analysis of a skin biopsy from the back revealed neutrophilic suppurative folliculitis. Therefore, she postponed regorafenib administration for 2 months and was treated with topical application of clindamycin phosphate hydrate, which was effective. Consistent with reported evidence that the presence of acneiform eruption and the efficacy of EGFR inhibitors are positively associated, regorafenib had good anticancer activity in our patient. Ultimately, we found that although regorafenib-associated skin toxicities usually appear within 1 month of treatment, patients potentially can present with delayed-onset acneiform eruptions even 24 months later.